Streamlining Electrical Distribution Using LVMDP Panels in Indonesia: Merampingkan Distribusi Listrik Menggunakan Panel LVMDP di Indonesia - Dwi, Achmad Arif; Falah, Agus Hayatal (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the efficiency of load balancing in Low Voltage Main Distribution Panels (LVMDP) through an industrial internship program for Electrical Engineering students. Utilizing a descriptive methodology with observation-based data collection, the research highlights the distribution of power across R-S-T phases—12,944.00 W, 12,912.00 W, and 13,032.00 W, respectively—demonstrating a nearly balanced load. The findings suggest that practical training can significantly enhance understanding and management of electrical panels, offering crucial insights into improving electrical distribution systems globally. Highlights: Hands-on Training: Students gain practical experience in electrical panel manufacturing, enhancing their skills and understanding of real-world applications. Critical Infrastructure: LVMDP panels play a crucial role in ensuring efficient and safe electricity distribution within buildings, emphasizing the importance of their construction and maintenance. Data-Driven Analysis: The descriptive method and observational data collection provide insights into power needs and load sharing, facilitating informed decision-making for electrical system optimization. Keywords: Panel, LVMDP, Planning